Paravertebral muscle training in patients with unstable spinal metastases receiving palliative radiotherapy: an exploratory randomized feasibility trial - Sprave, Tetyana; Rosenberger, Friederike; Verma, Vivek; Förster, Robert; Bruckner, Thomas; Schlampp, Ingmar; Bostel, Tilman; Welzel, Thomas; Akbaba, Sati; Rackwitz, Tilmann; Nicolay, Nils; Grosu, Anca-Ligia; et al. (Cancers, 2019)
Background: Isometric paravertebral muscle training (IPMT) may improve mobility, pain, and quality of life (QOL) in cancer patients with spinal metastases. However, this regimen remains unproven in patients with unstable spinal metastases (USM), a population at high risk for clinical exacerbation with such interventions. Thus, we conducted this exploratory, non-blinded, randomized controlled trial (NCT02847754) to evaluate the safety/feasibility of IPMT and secondarily assess pain, bone density, pathologic fracture rate, and QOL. Methods: All patients had histologically/radiologically confirmed USM (per Taneichi score) and underwent non-operative management with 5–10 fractions of palliative radiotherapy (RT). Randomization (1:1) groups were IPMT (intervention, INT) or muscle relaxation (control, CON); both lasted 15 min/day and started concurrently with radiotherapy. The primary endpoint was feasibility (completion of training programs three months post-RT). Secondary endpoints were pain response (Visual Analog Scale) and opioid consumption, bone density and pathologic fracture rate, and QOL (European Organization for Research and Treatment of Cancer, EORTC questionnaires). Results: Sixty patients were randomized and 56 received protocol therapy. Mean survival in both groups was 4.4 months. There were no adverse events with either training regimen. Altogether, ≥80% of the planned sessions were completed by 55% (n = 16/29) in CON and 67% (n = 18/27) in INT. Regarding the post-radiotherapy home-based training, ≥80% of planned sessions were completed by 64% (n = 9/14) of the INT cohort. There were no differences in pain scores, opioid consumption, or bone density between arms (p > 0.05 for all). No difference was observed between groups regarding new pathological fractures (INT: n = 1 vs. CON: n = 3) after three months (p = 0.419). There were no QOL differences between arms (all parameters p > 0.05). Conclusions: IPMT is potentially feasible for high-risk USM patients. Future trials adequately powered for relevant endpoints are thus recommended.
Gesehen am 15.04.2020